A prospective study on the outcomes of in-hospital cardiac arrest cases receiving cardiopulmonary resuscitation in two tertiary hospitals in malaysia - Kwanhathai Darin, Wong (2008)
Resuscitation medicine is an integral part of acute emergency care. The advancement in this field has led to evidence-based international guidelines on the practice of CPR which has improved and standardized its practice. Coupled with the usage of the Utstein style to report on outcomes of CPR, this has further enhanced increasing standardized research in this arena. However, it remains to be proven whether these results of research mainly from other countries is applicable to our local population. There is currently a severe lack of CPR research in Malaysia. This study aims to tackle this by investigating the rates of survival outcomes for in-hospital cardiac arrest (IJ-IA) in our population. This study also serves as a starting point to hopefully create a database that other centers in the nation will be able to add on to. The objective of this study is to determine the outcomes of CPR in In-Hospital Cardiac Arrest (IHA) cases. The endpoints are looking at the success rate of achieving ROSC (return of spontaneous c irculation), immediate survival (ROSC at least 20 minutes), 24-hour survival and survival-to-hospital discharge. Another objective is to identify any factors that could lead to the improvement in these endpoints. This is a prospective study using convenient sampling. It was conducted from March, 2007 until December, 2007. The standard Utstein in-hospital CPR reporting form was distributed to all locations involved in this study and a briefing was given to all the staff involved in these areas at the beginning of the study. Any case of IHA requiring CPR in these areas was then included into the study and a member of the primary resuscitating team would fill in the form . The forms were then collected and the fo llow up of the patients that survived were then conducted until the patients were discharged from hospital or passed away in hospital. In this study, survival outcomes for IHA receiving CPR obtained were a rate of ROSC of 61 .2% (n=60), immediate survival rate of 38.8% (n=38), 24-hour survival of 14.3% (n=l 4) and a survival-to-discharge rate of8.16% (n=8). The mean age ofthe study population was 50 years and 59% were in the middle-age range of 40 to 70 years. The males outnumbered females by a ratio of 2.1 : 1. Majority of THA events were monitored (91 %) and witnessed (99%). The main immediate causes of arrest were hypotension (4 1.8%), myocardial infarction ( 19.4%) and respiratory depression (17.3%). When divided into cardiac causes versus noncardiac, the percentages were 29.6% vs 70.4% respectively. The time from collapse to CPR was less than I minute in 76.5%. The initial rhythms detected at THA were bradycardia (n=31 ), asystole (n =28) and PEA (n=27). The immediate survival of day time versus night time THA was 45 .6% vs 29.3%. The other survival rates were not affected by time of THA. The only significant factor associated with 24-hour survival and survival-to-discharge was having a shockable rhythm at time of arrest. In conclusion, the survival outcomes for lHA with CPR obtained were a rate of return of spontaneous circulation (ROSC) of 61.2% (n=60), immediate survival rate of 38.8% (n=38), 24-hour survival of 14.3% (n= l4) and a survival-to-discharge rate of 8.16% (n=8). A shockable rhythm at the time of IHA was the only significant factor to affect outcomes.